Role of T-lymphocytes in production of antibody to antigens of Rickettsia tsutsugamushi and other Rickettsia species. - Jerrells, T R (1983)
The requirement of thymus-dependent lymphocytes for antibody production to Rickettsia tsutsugamushi, Rickettsia akari, Rickettsia conorii, and Rickettsia typhi was investigated by comparing antibody production in athymic (nu/nu) or thymus-bearing BALB/c mice. Athymic BALB/c mice produced antibody after infection with R. akari, R. conorii, and R. typhi as measured by indirect fluorescent antibody titration or radioimmunoassay. Antibody production in these mice was a great or greater than in the thymus-bearing mice and demonstrated similar kinetics. In contrast, athymic BALB/c mice infected either intraperitoneally or subcutaneously with the Gilliam strain of R. tsutsugamushi failed to produce demonstrable antibody. The requirement of thymus-dependent lymphocytes for antibody production to R. tsutsugamushi was further suggested by the demonstration of antibody production after transfer of immune thymus-dependent lymphocytes to athymic mice and the demonstration of R. tsutsugamushi-specific T helper cells in immune thymus-bearing mice. The antibody produced in athymic mice after infection with R. akari, R. conorii, and R. typhi was predominantly immunoglobulin M, based on isotype-specific radioimmunoassays and sucrose gradient fractionation. Furthermore, the antibody produced by athymic mice in response to R. akari infection reacted with a carbohydrate-containing outer membrane component.